Personal And Social Responsibility And Physical Activity Participation In Students - Bernardino Javier Sánchez-Alcaraz Martínez; Estefania Ros García; Manuel Alfonso-Asencio; Marta Hellín-Martínez; Alberto Gómez-Mármol (Federación Extremeña de Balonmano; University of Extremadura, 2021)
The aim of this paper was to analyse the levels of personal and social responsibility and physical activity participation according to students' gender and Education Stage, and to know the relationship between these two variables. The sample consisted on 344 students (152 boys y 192 girls), between 11 and 17 years old (M = 14.03; SD= 2.15), corresponding to Primary Education Stage (N = 174) and Secondary Education Stage (N = 170), who were administered the Personal and Social Responsibility Questionnaire and the Physician-based Assessment and Counseling for Exercise. The results showed significantly higher values of personal responsibility and physical activity in boys. Thus, primary stage students showed significant higher values on personal responsibility, helping others, and physical activity than secondary stage students. Finally, the practice of physical activity was positively and significantly associated with the personal and social responsibility of the students. These data can help teachers and coaches to promote values through physical activity.